THE NEED ANALYSIS OF INTERACTIVE MULTIMEDIA DEVELOPMENT USING ADOBE FLASH FOR SENIOR HIGH SCHOOL - Ade Oktaviani Sinaga; Ardi Ardi; Erma Erma (Universitas Negeri Padang, 2021)
The purpose of this research is to collect initial information to develop interactive multimedia based on Adobe Flash. The type of research used in this research is descriptive quantitative research. The method used to collect data was done through interviews with biology teachers and distributing observation questionnaires to students of class XI MIPA. In addition, the results of daily tests obtained by students are also used as data in this study. The results of the study revealed that students had difficulty in understanding the material on Cells and Cell Bioprocess, this is because this material has many submaterials and is abstract. In addition, the media used by the teacher is also not effective in overcoming the learning difficulties of students, as well as the varied learning styles of students. This makes students look less active and causes the low value of student learning outcomes or is still under the Minimum Completeness Criteria (KKM). Therefore, interactive multimedia based on Adobe Flash is needed on Cells and Cell Bioprocess materials for class XI SMA/MA.